Pengaruh Pengunaan Metode Pembelajaran Ceramah dan Card Sort Pada Mata Pelajaran Sejarah Kebudayaan Islam Materi Prestasi-prestasi Khulafaur Rasyidin - Haryadi, Joni; Maria, Haratua Tiur; Karolina, Venny (Jurnal Ilmiah Wahana Pendidikan, 2024)
The research method used is included in the experimental category, and the data analysis process was carried out using the SPSS application. The aim of this research is to find out whether there are differences in learning outcomes for SKI subjects using the lecture and card sort methods. The statistical analysis used is the Independent t-test (if the data is normal) or the Mann-Whitney U test (if the data is not normal). The research population included class VII students at MTs Negeri 2 Mempawah, with a research sample of 10 students who were divided into two groups, namely the group treated with the lecture method (class A) and the group treated with the card sort method (class B). After the second group received treatment, the researcher carried out a test regarding the learning outcomes of the subject "History of Islamic Culture" with a focus on the material "Khulafaur Rasyidin's Achievements". Learning outcomes are measured by giving 10 multiple choice questions, with the highest score being 100 and the lowest being 0. The research results show that there is no significant difference or influence on student learning outcomes, whether using the lecture or card sort method. Therefore, it can be concluded that the two learning methods, namely lecture and card sort, are effective in improving student learning achievement in the history of Islamic culture subject by focusing on the material achievements of Khulafaur Rasyidin